Study of the innovative ideas in electric cars and the environmental impacts challenges - LAGGOUN ABDESSAMED; BENAIDA, BACHIR NACERELLAH; Mahdjoubi, Abdel Halim (Université Amar Telidji de Laghouat Faculté des Sciences et Technologie; Département Électrotechnique, 2024)
In this work, we have studied the electric cars in terms of renewal and newly invented ideas that have contributed and continue to contribute to the development of performance in terms of battery capacity and user comfort. We have mentioned 11 ideas included in terms of energy source and distribution and even transmission to reach the profit appearance of any idea outside the box, taking into account the climate challenges, warnings of organizations about global warming and the need for Energy Transition, which included the most important challenges of electric cars and battery materials and the differences with combustion interne cars.
Electrotechnique industrielle